Power plant waste heat utilisation for desalination plant [electronic resource] - Ayad Ali Taleb Mohammed, 1988-; Farid Nasir Ani, supervisor; Fakulti Kejuruteraan Mekanikal (2013)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2013